Providing pediatric well-care and sick visits in the COVID-19 pandemic era: the recommendations of the Italian pediatric society - Rino Agostiniani; Elena Bozzola; Annamaria Staiano; Antonio Del Vecchio; Teresa Mazzone; Luigi Greco; Giovanni Corsello; Alberto Villani (BMC, 2020)
Abstract Pediatricians have observed a significant decrease in in-person child health visits during the COVID-19 pandemic. In the post lockdown period, the coronavirus trend remains positive in Italy but fears of a second wave have recently grown in Italy due to active hotbeds of contagion. The pandemic may negatively affect the care of pediatric patients and overall children welfare as it may present with severe signs and symptoms or it may complicate. The Italian Pediatric Society recommend to separate well visits from sick ones, to educate families and to promote hygienic strategies to provide an adequate pediatric assistance in case of a second pandemic wave.